UJI SELEKTIFITAS TRANSPOR Cu(II) TERHADAP Mg(II), Ca(II) DAN Sr(II) DENGAN ZAT PEMBAWA OKSIN DAN SDS SEBAGAI ADITIF MELALUI TEKNIK MEMBRAN CAIR FASA RUAH - Olly Norita Tetra; Zaharasmi Kahar; Admin Alif; - Frengky (Jurnal Riset Kimia, 2012)
Selectivity of Cu(II) transport from the source phase containing Mg(II), Ca(II) and Sr(II) into the receiver phase had been researched by using oxine as carrier and Sodium Dodecyl Sulfate (SDS) as additive through bulk liquid membrane.The efficiency of the method depends on parameter (the pH of the donor and acceptor phase, effect of carrier concentrations, and time of transport). The selectivity of the method was assessed by performing the single, as well as the competitive transport experiment of Mg(II), Ca(II,) and Sr(II) ion and then Cu(II) percentage which was transported to receiver phase 99.98% and residue in source phase do not detect. The measurement was done to both of source phase and receiver phase by using Atomic Absorption Spectrophotometer (213.9 nm).